Foreign accent : the phenomenon of non-native speech - Moyer, Alene, 1961- (Cambridge : Cambridge University Press, 2013)
'To what extent do our accents determine the way we are perceived by others? Is foreign accent inevitably associated with social stigma? Accent is a matter of great public interest given the impact of migration on national and global affairs, but until now, applied linguistics research has treated accent largely as a theoretical puzzle. In this fascinating account, Alene Moyer examines the social, psychological, educational and legal ramifications of sounding'foreign'. She explores how accent operates contextually through analysis of issues such as: the neuro-cognitive constraints on phonological acquisition, individual factors that contribute to the'intractability' of accent, foreign accent as a criterion for workplace discrimination, and the efficacy of instruction for improving pronunciation. This holistic treatment of second language accent is an essential resource for graduate students and researchers interested in applied linguistics, bilingualism and foreign language education'--
1. The scope and relevance of accent -- 2. Accent and age -- 3. Accent and the individual -- 4. Accent and society -- 5. Accent and the law -- 6. Accent and instruction -- 7. Conclusions.
Includes bibliographical references (pages 184-216) and index.
Keywords: English language -- Pronunciation by foreign speakers; Second language acquisition -- Social aspects; Languages in contact